Razvojni program za trajnostni razvoj krajev območja mesta Čabar v Gorskem kotarju: II. faza - admin; Čeligoj, Vladimir; Ožbolt, Zoran; Koščak, Marko (2019)
The development program for the sustainable development of town Čabar in Gorski kotar: Phase II. This book is the result of the second phase of the project, with which we want to stimulate the sustainability and strategic development of the Croatian border area of the town Čabar. The area is distant from the main roads, but at the same time it is located between three countries (Croatia, Slovenia and Italy), which has always been a source of employment, information and social life for the locals. The intertwining of different traditions enabled the creation of an autochthonous culture that combines interesting customs, crafts, dishes and the use of natural resources from the unspoiled nature. All of this is an excellent basis for the development of tourism, which can improve the economy, reverse the demographic picture and stimulate the overall development of the area. This challenge was addressed by tutors and students of the Tourism Master's program at the Faculty of Tourism University of Maribor together by participatory planning and involvement of local community. After the analysis of the situation, they prepared a development vision, identified work priority areas, defined the indicators and the way they would be monitored. The action plan itself is based on the theory of carrying capacity assessment, presented at the beginning of this book.
Keywords: Gorski kotar; sustainable development; development program; carrying capacity assessment; tourism